Exploring Financial Management Strategies: A Descriptive Qualitative Inquiry with Literature Review - Nurwanah, Andi; Junaid, Asriani; Kalsum, Ummu; Ikhtiari, Kirana; Muslim, Muslim (The Journal of Business and Management Research, 2023)
This study delves into financial management strategies through a qualitative approach to uncover insights into investment decisions, financing choices, and dividend policies within organizations. The research employs purposive sampling to select relevant literature from diverse sources, including academic journals and books. Data collection involves a systematic review and analysis of the existing literature to find meaningful patterns and trends. The study reveals significant findings regarding the importance of investment decisions in allocating capital effectively, the role of capital budgeting in evaluating investment opportunities, and the influence of external factors on investment decisions. Additionally, the study highlights the multifaceted nature of financing decisions, emphasizing the significance of capital structure optimization and cost of capital management. Furthermore, insights into dividend policy decisions underscore the importance of aligning dividend distributions with organizational objectives and stakeholder interests. Overall, this research contributes to a deeper understanding of financial management strategies and provides valuable guidance for practitioners and scholars seeking to enhance financial decision-making processes.